2018
DOI: 10.21767/2471-8084.100070
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity of Paraquat Dichloride and Ameliorative Effect of Nutritional Supplements

Abstract: This study determined the potential hepatotoxicity of Paraquat dichloride (PQ) and ameliorative effect of selected nutritional supplements. Male Wistar albino rats were intraperitoneally administered sub-lethal concentration of Paraquat dichloride (1.5 mg/kg body weight) at alternate days and concomitantly treated daily with nutritional supplements (glutathione, vitamin C and garlic) for three weeks. Hepatotoxic and protective effect of PQ and nutritional supplements were respectively determined by assay of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The role of pesticides in the etiology of liver ailments has been well‐documented (Karami‐Mohajeri et al., 2017; Manfo et al., 2020). For example, in animal studies, rats exposed to the copper‐based fungicides, fipronil, and paraquat dichloride presented with oxidative damage and liver injury (Gad El‐Hak & Mobarak, 2018; Kartheek & David, 2018; Ujowundu et al., 2018). Other pesticides, such as imidacloprid (Arfat et al., 2014) and Fenitrothion (Ehsan et al., 2014), caused a hepatic injury in mice and fish models of animal experimentation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The role of pesticides in the etiology of liver ailments has been well‐documented (Karami‐Mohajeri et al., 2017; Manfo et al., 2020). For example, in animal studies, rats exposed to the copper‐based fungicides, fipronil, and paraquat dichloride presented with oxidative damage and liver injury (Gad El‐Hak & Mobarak, 2018; Kartheek & David, 2018; Ujowundu et al., 2018). Other pesticides, such as imidacloprid (Arfat et al., 2014) and Fenitrothion (Ehsan et al., 2014), caused a hepatic injury in mice and fish models of animal experimentation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Paraquat cause toxicity occurs through the process of oxidative stress due to the exceeds production of Reactive Oxygen Species (ROS) (Ujowundu et al, 2018). Reactive oxygen species can cause damage to the structural membranes of renal tubular cells through the mechanism of lipid peroxidation (Tomsa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Later studies have observed the similar phenomenon [1,7,118]. [127][128][129][130][131] HMPs are also poisoned by biological factors including bacteria, fungi, yeast, and parasites with their spores and some toxins, which can easily cause misunderstandings about the actual advantage of some medicinal herbs. Among reported toxic elements, mycotoxins, a group of toxic secondary metabolites, which are primarily produced by Aspergillus, Penicillium, Fusarium, Claviceps, and Alternaria fungi.…”
Section: Nonphyto-hepatotoxins From Hmpsmentioning
confidence: 93%
“…However, overuse of these synthetic substances may have a long influence on environmental pollution and human health issues. The reported liver effects of pesticide and herbicide residues include hepatocellular hypertrophy and cytoplasm degeneration, obstructive cholestasis, decreased acetylcholinesterase activity, and hepatic mitochondrial toxicity [ 114 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ].…”
Section: Nonphyto-hepatotoxins From Hmpsmentioning
confidence: 99%